Development of Real-Time Monitoring System for an Off-Grid Photovoltaic System. Issue 1 (November 2021) - Sesa, M; Mahmuddin, F
Abstract: In operating a photovoltaic system, it is required to employ hardware and software systems to monitor the parameter of the results of the solar panel conversion. Usually, monitoring the photovoltaic system is done by manual gauges and recording the measured results manually which would require a human hand. The present research designed and developed a real-time monitoring system for an off-grid photovoltaic system that could monitor the photovoltaic system performance automatically. The monitoring system design has 2 (two) subsystems. The first subsystem is a hardware system in the form of an electronic data logger system equipped with an SD card. This allowed data to be recorded on an SD card. The second sub-system is a software design developed using Microsoft in Visual Basic. The hardware and software were connected to monitor the photovoltaic results and recorded the obtained data in an SD card for further analysis.